DETERMINAN SUSTAINABILITY REPORT DISCLOSURE PADA PERUSAHAAN LQ45 DI BURSA EFEK INDONESIA - Dewi Cahyati (2021)
This research is quantitative study which aimed to determine the effect of profitability as measured by return on assets, the size of the company measured by the logarithm natural of total assets and leverage as measured by debt to assets on sustainability report disclosure as measured by sustainability report disclosure index on LQ45 company in Indonesia Stock Exchange in the 2016-2020 research year. The population for this study were all LQ45 companies in Indonesia Stock Exchange. The samples for this study were 12 companies selected using purposive sampling method. The analysis technique used is Panel Data Regression Analysis with programs E-Views 10 and Microsoft Excel 2019. This study proves that profitability has no effect on sustainability report disclosure, and firm size has positive and significant effect on sustainability report disclosure, while leverage has negative and significant effect on sustainability report disclosure Keywords: Profitability, Company Size, Leverage and Sustainability Report Disclosure